Self-harm following release from incarceration: Patterns and measurement issues - Borschmann, Rohan; Young, Jesse; Kinner, Stuart; Spittal, Matthew (International Journal of Population Data Science, 2018)
Introduction Despite an elevated prevalence of self-harm in the incarcerated adult population, little is known about patterns of self-harm following release from prison. Objectives and Approach Baseline self-report interviews with 1315 adults immediately prior to release from prison in Queensland, Australia, combined with interrogation of linked health data from >3750 post-release emergency department presentations, >2000 ambulance attendances, and corrections data during periods of re-incarceration. Results Approximately 5% of all contacts with medical emergency services following release from prison resulted from self-harm. These were associated with being Indigenous, having a lifetime history of a mental disorder and having been identified by prison staff as being at risk of self-harm. Agreement between self-reported self-harm and medically-verified episodes of self-harm was poor. Conclusion/Implications Emergency services contacts resulting from self-harm following release from prison are common and represent an opportunity for tertiary intervention for self-harm. Our findings suggest that a self-reported history of self-harm should not be considered a reliable indicator of prior self-harm, or of future self-harm risk, in incarcerated adults.